REPORTING TENDENCIES RESTRICTIONS ON WNA ENTRY PERMITS TO INDONESIA DUE TO THE EMERGENCE OF NEW VARIANT COVID-19 OMICRON - Guntur Widyanto; Nur Afifah Putri (Polteknik Imigrasi, 2021)
The Government of the Republic of Indonesia has issued the latest regulations regarding restrictions on granting entry permits and residence permits for foreign nationals who in the last 14 days have visited 11 countries that have been exposed to the Omicron Covid-19 variant to enter Indonesian territory with purpose to prevent the entry of a new variant of Covid-19 B.1.1.529 or known as Omicron. This regulation elicited various responses from the public and the media. This study aims to examine how the online media Kompas.com and detik.com framing the news regarding the issuance of this latest regulation. This study is qualitative study with framing analysis by Robert N. Entman method. The results show that the online media Kompas.com and detik.com have a positive tendency in responding to the emergence of regulations regarding restrictions on entry permits and residence permits for foreigners. This is shown by the delivery of the narrative that the issuance of the regulation is an effort to prevent the entry of the Omicron Covid-19 variant into the Indonesian Territory.